Quantifying paraspinal muscle tone and stiffness in young adults with chronic low back pain: a reliability study - Hu, Xiaoqian (Sci Rep, 2018)
The reliability of a handheld myotonometer when used in a clinical setting to assess paraspinal muscle mechanical properties is unclear. This study aimed to investigate the between-session intra-rater reliability of a handheld myotonometer in young adults with low back pain (LBP) in a clinical environment. One assessor recorded lumbar paraspinal muscle tone and stiffness in an outpatient department on two occasions. The intraclass correlation coefficient (ICC), standard error of measurement (SEM), smallest real difference (SRD) and Bland-Altman analysis were conducted to assess reliability. The results indicated acceptable between-days intra-rater reliability (ICC > 0.75) for all measurements. The SEM of the muscle tone and stiffness measurements ranged between 0.20–0.66 Hz and 7.91–16.51 N/m, respectively. The SRD was 0.44–1.83 Hz for muscle tone and 21.93–52.87 N/m for muscle stiffness. SEM and SRD at L(1)-L(2) were higher than those at other levels. The magnitude of agreement appeared to decrease as muscle tone and stiffness increased. The myotonometer demonstrated acceptable reliability when used in a clinical setting in young adults with chronic LBP. Measurements of the upper lumbar levels were not as reliable as those of the lower lumbar levels. The crural attachment of the diaphragm at L(1) and L(2) may affect paraspinal muscle tone and stiffness during respiratory cycles.